What does recovery mean to a forensic mental health patient? A systematic review and narrative synthesis of the qualitative literature. Issue 1 (2nd January 2016) - Clarke, C.; Lumbard, D.; Sambrook, S.; Kerr, K.
Abstract: This is a systematic review and narrative synthesis of qualitative literature for forensic mental health patients' perceptions of recovery. Relevant databases were searched and a total of 11 studies that fit the inclusion criteria were identified. Thematic Synthesis was applied to synthesise the collated themes into six superordinate themes: connectedness, sense of self, coming to terms with the past, freedom, hope and health and intervention. Two superordinate themes were particularly prevalent: connectedness and a sense of self. It is argued that a focus on increasing opportunities for forensic mental health patients to develop a sense of self and connectedness could help improve recovery. Future recommendations to expand on these findings include using grounded theory methods to develop theoretical understanding of the data.